Pesantren Virtual Di Masa Pandemik - Mokhammad Nizam (Pedir Research Institute, 2021)
Abstract: The Covid-19 pandemic has changed the paradigm of Indonesian education, not least in Islamic boarding schools. Identical to the traditional bandongan and wetonan systems for centuries, now pesantren also have to implement e-learning to carry out their educational functions for students who are in their respective homes. In a qualitative descriptive design, this article aims to analyze the implementation of e-learning for a month at the Amanatul Ummah Islamic Boarding School, Mojokerto, East Java, both in formal and early school learning. The author also tries to contextualize the implementation of e-learning with several principles in the world of Islamic boarding schools as a valid argument.